ANALISIS KORELASI STRES AKADEMIK PADA HASIL BELAJAR KOGNITIF BIOLOGI BERDASARKAN JENIS KELAMIN SANTRI ASRAMA DI SMAIT IHSANUL FIKRI MUNGKID - Vannya Rachma Ariarizky; Karunia Galih Permadani; Setiyo Prajoko (Bio-Lectura : Jurnal Pendidikan Biologi, 2023)
This study aims to determine the correlation of academic stress to cognitive biology learning outcomes based on the gender of boarding students at SMAIT Ihsanul Fikri Mungkid. The research method used is quantitative correlational type. The population in this study was class XII science students at SMAIT Ihsanul Fikri Mungkid. The research sample was 96 students consisting of 48 male and 48 female samples and was taken by random sampling technique. The results showed that female had a negative correlation between academic stress and learning outcomes with the "sufficient" category to biological cognitive learning outcomes of -0.447 compared to malewho did not correlate with biological cognitive learning outcomes of 0.253.